Early Engagement in the View of the Shafi‘i Madhhab and Positive Law in Bangkalan Community, Indonesia - M. Ridoi; Siti Masruchah; Shofiatul Jannah (KURAS Institute, 2025)
In Bangkalan Regency, there is a phenomenon of early engagement where children aged 0-6 years are matched by their parents or families without involving the children. This situation becomes problematic when individuals involved in adult engagements do not find a match, which often leads to the cancellation of the engagement. This cancellation can cause a rift between the couple and the family, and has negative impacts such as the loss of individual freedom, hindered education, and potential psychological trauma. This study highlights the potential risks associated with underage engagement to seek the law on early engagement as it occurs in Bangkalan from the perspective of the Shafi'i school of thought and positive law. The research method in this thesis uses a phenomenological method, to gain an understanding of the social reality that occurs in the community, then examined from the perspective of the Shafi'i school of thought and positive law. The results show that early engagement in Bangkalan Regency is considered halal according to the Shafi'i school of thought and positive law, as long as it meets two conditions: the relationship between a man and a woman who are not mahram, and the woman is not engaged to another person. Although legal, it is recommended that engagements not be conducted with minors to prevent potential detrimental risks.